2014
DOI: 10.1111/ffe.12201
|View full text |Cite
|
Sign up to set email alerts
|

High‐cycle fatigue properties of beta Ti alloy 55Ti–30Nb–10Ta–5Zr, gum metal

Abstract: A B S T R A C T This paper describes the fatigue properties of the beta titanium alloy 55Ti-30Nb-10Ta-5Zr, generally referred to as 'Gum Metal'. Rotating bending fatigue tests have been performed in laboratory air and in a 3% NaCl aqueous solution. The results obtained were compared with those of a conventional beta titanium alloy, Ti-22V-4Al. In tensile tests, 55Ti-30Nb-10Ta-5Zr indicated elasticity and microplasticity in the elastic region. Thus, the elastic modulus slightly decreased with an increasing stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…Some other contributions focused on the fatigue behaviour of titanium alloys have been published recently in this journal …”
Section: A Synthesis In Terms Of Linear Elastic Sed Averaged Over a Cmentioning
confidence: 99%
“…Some other contributions focused on the fatigue behaviour of titanium alloys have been published recently in this journal …”
Section: A Synthesis In Terms Of Linear Elastic Sed Averaged Over a Cmentioning
confidence: 99%
“…The effect of corrosive body environment on fatigue life of β Ti alloys has also been investigated [86,98,146,149,150,152]. A few reports suggested that high cycle fatigue strength of β Ti alloys is similar in air and in corrosive environments that simulate body conditions [146,149,152]. This is likely due to the high corrosion resistance of Ti alloys.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Nevertheless, fatigue strengths of several newly developed orthopedic β Ti alloys remain uncharacterised. Very limited comprehensive information is available on properties such as strain-controlled fatigue tests, crack growth of long cracks and small cracks, notch fatigue strengths, and fretting fatigue among others [98,152]. The effect of processing β Ti alloys by SPD and AM on fatigue response are wide open for research.…”
Section: Performance Evaluation Of β Ti Alloysmentioning
confidence: 99%
See 1 more Smart Citation